If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
Y = (1/3)*x-100 // - (1/3)*x-100
Y-((1/3)*x)+100 = 0
Y+(-1/3)*x+100 = 0
Y-1/3*x+100 = 0 // - Y+100
-1/3*x = -(Y+100) // : -1/3
x = (-(Y+100))/(-1/3)
x = 3*(Y+100)
x = 3*(Y+100)
| 1/3×251.2 | | 8y-30-2y=6(y-5) | | 8y+14-1y=7(y+2) | | 60=20/x | | 8y+14=7(y+2) | | x^2+bx-42= | | 24+36+x=180 | | 3xb=0.85 | | 6x^2+56x-9=0 | | 4(X^2+121)+64=16 | | 15P/45=180 | | r/j-8=-3v/j | | x^2-bx+21= | | (-9^3y^4)(1/3x^5)(-2y^2) | | Y=3(X-7) | | (-93y4)(1/3x5)(-2y2) | | v^2=40 | | -4=2a^2-3a | | 6x-30-1x=5(x-6) | | 3x-5=10x+11 | | 8+5(x)=10 | | 0.3(x+50)-0.02(x-10)=-1.6 | | (9/25)^3x= | | -15+u=-28 | | 7y+15-2y=5(y+3) | | 7y+15-2y=7(y+3) | | 2/3(-21/16) | | (9/25)^3x=3125/243 | | 3n^2-24n+49=0 | | 7y+3-2y=5(y+3) | | 7y+15=5(y+3) | | 6z-36-2z=4(z-9) |